2022-RA-910-ESGO Malignant struma ovarii: an up-date on the current literature. (20th October 2022) - Giovannopoulou, Eirini; Saliaris, Konstantinos; Pandraklakis, Anastasios; Lathouras, Konstantinos
Abstract : Introduction/Background: Malignant struma ovarii is a rare monodermal ovarian tumor, that may affect women in their reproductive years. Data regarding effective treatment are scarce and are primarily derived from small retrospective studies. Therefore, there is no consensus on optimal treatment for those patients. Methodology: This review serves to provide information on the latest literature available pertaining to the treatment modalities and prognostic factors of malignant struma ovarii. Data were derived from the search in medical databases (Pubmed, Cohrane, Clinicaltrials.gov) up-to-date. Results: Due to the rarity of malignant struma ovarii, there is a paucity in the current literature for high quality randomized controlled trials regarding optimal surgical management and adjuvant therapy. The best available evidence is derived from limited retrospective cohort analysis. Five (5) large retrospective cohort studies that were published within the last two years were analyzed. The overall survival seems to be negatively affected by specific histologic subtypes, poor differentiation, ascites, recurrences and ovarian capsular involvement. Radioactive therapy has no proven benefit on overall survival. However, it is documented that thyroidectomy in combination with radioactive therapy increases disease free survival, in comparison to surgery alone. Conclusion: In the absence of high-quality data from randomized controlled trials, a conservative surgical approach with adjuvant thyroidectomy and radioactive therapy seems a reasonable approach and is supported by the relevant literature.